2018
DOI: 10.3920/bm2017.0160
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentum UCO-979C strongly inhibited Helicobacter pylori SS1 in Meriones unguiculatus

Abstract: Searching for bacterial probiotics active upon Helicobacter pylori continue to be an important clinical challenge because of the increased prevalence of this highly priority pathogen in humans. In this work, we assess the in vivo anti-H. pylori SS1 (cagA+/vacAs2m2+) properties of a previously isolated human gastric probiotic strain Lactobacillus fermentum UCO-979C by using a Meriones unguiculatus (Mongolian gerbil) model. Animals were administered with a saline suspension of L. fermentum UCO-979C or H. pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The long-term administration of probiotics might have positive results in H. pylori infection, particularly in reducing the risk to develop diseases caused by the high levels of gastric inflammation [ 65 ]. Moreover, the results of the present work confirm previous results reported for this probiotic strain [ 21 , 22 , 26 , 50 , 66 , 67 ], which may even be considered as a potential immunobiotic capable of reducing the adhesion of H. pylori to the gastric mucosa and the inflammatory damage caused by this pathogen, modulating the immune responses at the intestinal mucosa and systemic levels [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…The long-term administration of probiotics might have positive results in H. pylori infection, particularly in reducing the risk to develop diseases caused by the high levels of gastric inflammation [ 65 ]. Moreover, the results of the present work confirm previous results reported for this probiotic strain [ 21 , 22 , 26 , 50 , 66 , 67 ], which may even be considered as a potential immunobiotic capable of reducing the adhesion of H. pylori to the gastric mucosa and the inflammatory damage caused by this pathogen, modulating the immune responses at the intestinal mucosa and systemic levels [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…This probiotic strain was selected between other of lactic acid bacteria isolated from human gastric tissue because of its remarkable anti-H. pylori properties [41]. The UCO-979C strain strongly inhibited the adhesion, growth and urease activity of H. pylori in AGS cells and Mongolian gerbils [16,42]. Moreover, L. fermentum UCO-979C was able to beneficially modulate the cytokine response of AGS cells and THP-1 macrophages after H. pylori challenge [17].…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with a gastric microbiome study in humans showing increased abundance of Lactobacillus in Hp -associated intestinal metaplasia and intestinal type of gastric cancer, compared with non-atrophic gastritis (Aviles-Jimenez et al, 2014) as well as the increased gastric Lactobacillus population in INS-GAS mouse model co-infected with Hp and limited commensals ( Bacteroides, Clostridium , and Lactobacillus ) that developed GIN (Lertpiriyapong et al, 2014). However, others have reported a probiotic Lactobacillus strain that inhibited the colonization of Hp in a Mongolian gerbil model (Merino et al, 2018). More relevant to biofilm-associated Hp , Khosravi et al (2014) reported that Streptococcus mitis induced Hp conversion to coccoid cells in co-culture studies and their proteomic analysis revealed a metabolic crosstalk between these two bacteria, suggesting a probable impact on Hp -associated carcinogenesis (Khosravi et al, 2016; Krzyżek, 2017).…”
Section: Potential Role Of Polymicrobial Biofilms In Carcinogenesismentioning
confidence: 99%